To Publish, Make Known and Sell or Promoting Printed Books in the Incunabula Period - Lucia Lichnerová (Z Badań nad Książką i Księgozbiorami Historycznymi, 2021)
The study To Publish, Make Known and Sell is based on verified existence of competition tensions between the 15th century typographers/publishers, related to the absence of functional regulatory tools of book production of the incunabula period. The increase in the number of book-printers within the relatively narrow geographical area, disregard of publishers’ privileges, the emergence of pirated reprints, as well as insufficient self-promotion on the book market through introducing novelties had concentrated typographers’ attention on devising new tools of securing their triumph in publisher’s competition – the so called book advertisements. The author has analysed 44 promotional posters of the incunabula period from several points of view and attempted to identify their design elements, which on the one hand showed signs of certain standardization, while on the other hand they were subject to personal creativity of their creator. She gives detailed overview of the circumstances of the origin, typographic design and contents of book advertisements of several kinds within the context of promoting either the existing or planned editions, of one edition or a group of books; specifically focusing on the unique types of advertising. In conclusion, the author cites the circumstances of the extinction of book advertisements related to the rise of the new promotional tool – booksellers’ catalogue and submits a bibliography of the book advertisements dating from the 15th century.